Ekspresi Perasaan Cinta Tokoh Utama dalam Drama Love Is Phantom - Akram, Andi Nurnisa Rofifah; Anwar, Fithyani (Vocational College of Diponegoro University, 2025)
This research aims to analyze the love languages portrayed by the main characters in the drama